Breakthrough: An illustrated autoethnographic narrative into professional identity and storytelling - Lum, Kristen; Mortensen Steagall, Marcos (DAT Journal, 2023)
This article presents a practice-led artistic research project focused on the creative process of a scripted and illustrated graphic novel that draws from autoethnographic methods to engage with high levels of originality. The project: Breakthrough: An illustrated autoethnographic narrative into professional identity and storytelling responds to a rhetorical question that asks: How can one express personal identity in the form of a graphic novel? The design outcome of this project is a published graphic novel which explores ideas surrounding identity, particularly professional identity and finding or rediscovering oneself. The novel’s storyline draws upon the researcher’s journey as an artist and illustrator, the experiences of losing and regaining creative passions and stimulus. The graphic novel’s creative process employs creative expression skills to conceptualise and visualise the narrative. The design outcome is intended to resonate with others studying or working in creative industries and inspire young creatives in their journeys. The research project contributes to discourses about using ethnographic methods to engage originality in producing visual communication design outcomes underpinned by personal novelties and meaning. Additionally, it contributes to understanding practice-led research methodologies and the exegetical writing that supports a design artefact.